Hydroxychloroquine attenuates renal ischemia/reperfusion injury by inhibiting cathepsin mediated NLRP3 inflammasome activation - Tang, Tao-Tao; Lv, Lin-Li; Pan, Ming-Ming; Wen, Yi; Wang, Bin; Li, Zuo-Lin; Wu, Min; Wang, Feng-Mei; Crowley, Steve D; Liu, Bi-Cheng (Cell death & disease, 2018)
Inflammation is a major contributor to the pathogenesis of ischemic acute kidney injury (AKI), which complicates the post-operative outcomes of large numbers of hospitalized surgical patients. Hydroxychloroquine (HCQ), a well-known anti-malarial drug, is commonly used in clinical practice for its anti-inflammatory actions. However, little is known about its role in renal ischemia/reperfusion (I/R) injury. In the current study, mice were subjected to I/R injury and HCQ was administered for seven days by gavage prior to surgery. In parallel, HK-2 human renal proximal tubule cells were prophylactically treated with HCQ and then were exposed to hypoxia/reoxygenation (H/R). The results showed that HCQ significantly attenuated renal dysfunction evidenced by blunted decreases in serum creatinine and kidney injury molecular-1 expression and the improvement of HK-2 cell viability. Additionally, HCQ markedly reduced macrophage and neutrophil infiltration, pro-inflammatory cytokine production, and NLRP3 inflammasome activation. Mechanistic studies showed that HCQ could inhibit the priming of the NLRP3 inflammasome by down-regulating I/R or H/R-induced NF-κB signaling. Moreover, HCQ reduced cathepsin (CTS) B, CTSD and CTSL activity, and their redistribution from lysosomes to cytoplasm. CTSB and CTSL (not CTSD) were implicated in I/R triggered NLRP3 inflammasome activation. Notably, we found that HCQ attenuated renal injury through downregulation of CTSB and CTSL-mediated NLRP3 inflammasome activation. This study provides new insights into the anti-inflammatory effect of HCQ in the treatment of AKI.